The status of Islam and Islamic Law in the Malaysian Federal Constitution - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (Springer NAture Singapore Pte. Ltd., 2021)
The Malaysian Federal Constitution was drafted by ‘The Reid Commission’ headed by Lord William Reid, a distinguished Lord of Appeal in ordinary in the House of Lords, with other constitutional law experts, namely, Sir. Ivor Jennings (the United Kingdom), Sir. William McKell (Australia), Mr. Justice B. Malik (India), and Mr. Justice Abdul Hamid (Pakistan). The Federal Constitution is the supreme law of the federation (The Malaysian Federal Constitution (MFC), art. 4(1)). It is a lengthy document extending to 183 articles and 13 schedules, covering various matters, such as the federal and state governments’ structure and powers, individual fundamental rights, citizenship, emergency powers, and religion of the federation. Malaysia is a federation that consists of the following thirteen states, namely, Johore, Kedah, Kelantan, Malacca, Negeri Sembilan, Pahang, Penang, Perak, Perlis, Sabah, Sarawak, Selangor and Terengganu; and three Federal Territories, namely, Kuala Lumpur, Putrajaya and Labuan (MFC, art. 1). Each of the thirteen states mentioned earlier has its constitution, which also has to be in line with the auspice of the Federal Constitution (Ahmad and Ali Mohamed 2020). And, the Federal Constitution itself serves as the constitution for all the three Federal Territories (MFC, Item 27, Federal List, Ninth Schedule).